Walnut ointment promotes full-thickness burning wound healing: role of linoleic acid - Dan Zhao; Jinli Xiao; Lijuan Qiang; Xingwang Deng; Jingjing An; Qing Zhang; Fang Zhao; Jiaxiang Ma; Chao Fang; Guangyu Guan; Yinsheng Wu; Yan Xie (Acta Cirúrgica Brasileira, 2022)
ABSTRACT Purpose: To investigate the active ingredients of walnut ointment (WO) and its mechanism in repairing wounds. Methods: The ingredients of WO were detected by gas chromatography–mass spectrometry. The effect of linoleic acid (LA) was tested by in vitro Alamar Blue (AB) reagent. Image J software, histological and immunohistochemical analysis were used to confirm the healing effect of LA in the porcine skin model. The animals were euthanized after the experiment by injection of pentobarbital sodium. Results: LA, 24% in WO, promotes keratinocytes and fibroblasts proliferation, which were 50.09% and 15.07% respectively higher than control (p < 0.05). The healing rate of the LA group (96.02% ± 2%, 98.58% ± 0.78%) was higher than the saline group (82.11% ± 3.37%, 88.72% ± 1.73%) at week 3 and week 4 (p < 0.05). The epidermal thickness of the LA was 0.16 ± 0.04 mm greater and the expression of the P63 and CK10 proteins was stronger in the LA group than the control (p < 0.05). Conclusions: LA, which is the main components in WO can promote full-thickness burning wounds (FBWs) by stimulating cell proliferation and differentiation.